2013
DOI: 10.1111/1742-6723.12040
|View full text |Cite
|
Sign up to set email alerts
|

Common laboratory tests predict imminent medical emergency team calls, intensive care unit admission or death in emergency department patients

Abstract: Commonly performed laboratory tests can help predict imminent MET calls, ICU admission or death in ED patients. Prospective investigations of the clinical utility of such predictions appear desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…One drawback to our current approach is that whilst many, if not all, non-elective admissions to 27 The same authors have also shown good discrimination in detecting to imminent ICU admission and imminent death, using the same technique. 28 These findings provide optimism that an LDT-EWS might be predictive of outcome even when a full set of biochemistry and haematology tests is not available for use in the calculation of an LDT-EWS value. This hypothesis clearly needs further testing.…”
Section: -6mentioning
confidence: 88%
“…One drawback to our current approach is that whilst many, if not all, non-elective admissions to 27 The same authors have also shown good discrimination in detecting to imminent ICU admission and imminent death, using the same technique. 28 These findings provide optimism that an LDT-EWS might be predictive of outcome even when a full set of biochemistry and haematology tests is not available for use in the calculation of an LDT-EWS value. This hypothesis clearly needs further testing.…”
Section: -6mentioning
confidence: 88%
“…Loekito and colleagues have published a retrospective observational study in this issue of Emergency Medicine Australasia that takes some initial steps towards facing this challenge. 1 Their study is the first of its kind. There are studies looking at selected groups of patients, or 'track and trigger' early warning systems largely based on physiological parameters or ICU-derived scoring systems, [2][3][4] but none that focus solely on laboratory tests in undifferentiated ED patients.…”
Section: -Neils Bohrmentioning
confidence: 99%
“…The sickest of the sick need emergency physicians when they arrive and then intensivists during their admission. Despite our best efforts, medical emergency team (MET) calls, intensive care unit (ICU) admissions and deaths still occur soon after admission to the ED . Perhaps if high‐risk patients could be reliably identified, then ICU review could occur earlier, end‐of‐life issues might be addressed urgently and timelier interventions instituted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The accessibility, turnaround time, reliability, and predictive ability of laboratory test results are crucial to the performance of emergency departments (EDs) in hospitals [ 1 4 ], and to the safety and quality of care provided by emergency physicians (EPs) [ 5 , 6 ]. Due to the specific nature of emergency medicine, EPs must rapidly investigate the state and stability of a patient’s health in order to make informed decisions and implement medical interventions that can make the difference between life and death.…”
Section: Introductionmentioning
confidence: 99%